2005
DOI: 10.1016/j.bandl.2004.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Lexical retrieval constrained by sound structure: The role of the left inferior frontal gyrus

Abstract: Positron emission tomography was used to investigate two competing hypotheses about the role of the left inferior frontal gyrus (IFG) in word generation. One proposes a domain-specific organization, with neural activation dependent on the type of information being processed, i.e., surface sound structure or semantic. The other proposes a process-specific organization, with activation dependent on processing demands, such as the amount of selection needed to decide between competing lexical alternatives. In a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…In word reconstruction tasks in which an auditory pseudoword has to be transformed into a real word by changing one phoneme, listeners prefer to preserve the consonantal structure over the vocalic one, so that kebra would be changed into cobra rather than zebra. Comparable results have been observed in English (van Ooijen, 1996;Sharp, Scott, Cutler & Wise, 2005), Dutch and Spanish (Cutler, Sebastián-Gallés, Soler-Vilageliu, & van Ooijen, 2000). Visual priming experiments, on the whole, also converge toward a consonantal priming effect, as attested by the results found using the relative-position (csn preceding casino is facilitatory, but not aio, Duñabeitia & Carreiras, 2011), the delayed-letter (e.g., bu-b or b-lb as primes preceding bulb, Vergara-Martínez et al, 2011) and the replaced-letter (e.g., duvo or rifa preceding diva, New, Araújo & Nazzi, 2008;New & Nazzi, in press) paradigms.…”
mentioning
confidence: 61%
“…In word reconstruction tasks in which an auditory pseudoword has to be transformed into a real word by changing one phoneme, listeners prefer to preserve the consonantal structure over the vocalic one, so that kebra would be changed into cobra rather than zebra. Comparable results have been observed in English (van Ooijen, 1996;Sharp, Scott, Cutler & Wise, 2005), Dutch and Spanish (Cutler, Sebastián-Gallés, Soler-Vilageliu, & van Ooijen, 2000). Visual priming experiments, on the whole, also converge toward a consonantal priming effect, as attested by the results found using the relative-position (csn preceding casino is facilitatory, but not aio, Duñabeitia & Carreiras, 2011), the delayed-letter (e.g., bu-b or b-lb as primes preceding bulb, Vergara-Martínez et al, 2011) and the replaced-letter (e.g., duvo or rifa preceding diva, New, Araújo & Nazzi, 2008;New & Nazzi, in press) paradigms.…”
mentioning
confidence: 61%
“…Studies using an oral word reconstruction task showed that when English-, Spanish-, or Dutch-speaking adults are required to change one phoneme so as to transform a pseudoword (e.g., teeble) into a word, they prefer to preserve the consonantal material and alter a vowel (e.g., table), a pattern suggesting that consonants are more stable than vowels in lexical access and activation processes (Cutler, Sebastián-Gallés, Soler-Vilageliu, & van Ooijen, 2000;van Ooijen, 1996). This link between consonants and the lexicon was confirmed in an equivalent positron emission tomography (PET) scan study, showing greater activation for consonant transformations in the left inferior frontal gyrus, an area involved in lexical search (Sharp, Scott, Cutler, & Wise, 2005). Finally, such a consonant bias was also found in many written lexical decision studies using a priming paradigm, showing more priming by consonantal than vocalic information (for Spanish : Carreiras, Dunabeitia, & Molinaro, 2009a;Carreiras, Gillon-Dowens, Vergara, & Perea, 2009b; for English: Lee, Rayner, & Pollatsek, 2002;for French: New, Araujo, & Nazzi, 2008).…”
Section: Introductionmentioning
confidence: 71%
“…Based on several cases of alexia-with-agraphia, Dejerine (1891) suggested that the inferior parietal lobule was a multimodal language region involved in both reading and writing, both of which require phonologically-based transformations between visual and auditory linguistic codes. Confirmation of a role for the inferior parietal lobule, and demonstration of a role for left inferior frontal cortex, in phonology has come from modern functional neuroimaging studies (Pugh et al, 1996;Gold and Buckner, 2002;Sharp et al, 2005). In addition, left inferior frontal cortex has been reported to show strong activation associated with phonological components of visual word recognition (Rumsey et al, 1997;Heim et al, 2005).…”
Section: Discussionmentioning
confidence: 98%